Project Innovation: Evidence‐Informed, Open, Effectual, and Subjective. Issue 2 (April 2016) - Huff, Anne Sigismund
ABSTRACT: Entrepreneurship provides promising bases for project innovation in unpredictable settings that require general adaptability rather than responsive variety. However, important theories in this area are based on world views that are antithetical to the causal assumptions that support often‐productive theory and practice in project management. This article outlines four entrepreneurial models of innovation, concluding with subjective innovations based on interactively defined lifestyle and ideological values rather than scientific or economic logic. Their adoption requires difficult personal and organizational admissions of failures in current practice as well as recognition that deeply rooted beliefs in causal logic are an impediment in intrinsically unpredictable environments.